Cyclometalated iridium(III) complex based on isoquinoline alkaloid synergistically elicits the ICD response and IDO inhibition via autophagy-dependent ferroptosis - Yuan Lu; Shan-Shan Wang; Meng-Ya Li; Rong Liu; Meng-Fan Zhu; Liang-Mei Yang; Feng-Yang Wang; Ke-Bin Huang; Hong Liang (Acta Pharmaceutica Sinica B)
The development of anticancer drugs to treat triple-negative breast cancer (TNBC) is an ongoing challenge. Immunogenic cell death (ICD) has garnered considerable interest worldwide as a promising synergistic modality for cancer chemoimmunotherapy. However, only few drugs or treatment modalities can trigger an ICD response and none of them exert a considerable clinical effect against TNBC. Therefore, new agents with potentially effective chemoimmunotherapeutic response are required. In this study, five new cyclometalated Ir(III) complexes containing isoquinoline alkaloid CˆN ligands were designed and synthesized. Among them, Ir-1 exhibited the highest in vitro cytotoxicity. Mechanistically, Ir-1 could trigger autophagy-dependent ferroptosis and a subsequent ferroptosis-dependent ICD response as well as indoleamine 2,3-dioxygenase (IDO) inhibition via reactive oxygen species (ROS)-mediated endoplasmic reticulum (ER) stress in MDA-MB-231 cells. When immunocompetent BALB/c mice were vaccinated with Ir-1-treated dying TNBC cells, antitumor CD8+ T-cell response and Foxp3+ T-cell depletion were induced, resulting in long-lasting antitumor immunity in TNBC cells. Moreover, combination therapy with Ir-1 and anti-PD1 could substantially augment in vivo therapeutic effects. Based on these results, Ir-1 is a promising candidate for chemoimmunotherapy against TNBC and its effects are mediated synergistically via ICD induction and IDO blockage.